Health-related quality of life in food-allergic adults from eight European countries. - Goossens, Nicole J; Flokstra-de Blok, Bertine M J; van der Meulen, Gerbrich N; Arnlind, Marianne H; Asero, Ricardo; Barreales, Laura; Burney, Peter; Cerecedo, Imnaculada; Clausen, Michael; Fernandéz-Rivas, Monteserrat; Frewer, Lynn; de la Hoz Caballer, Belén; et al. (Ann Allergy Asthma Immunol, 2014)
BACKGROUND: Food allergy can impair health-related quality of life (HRQL). Food Allergy Quality of Life Questionnaires (FAQLQs) have been developed and validated, including an adult form (FAQLQ-AF). HRQL has not, to date, been measured across different European countries using a uniform methodology. OBJECTIVE: To translate and validate the FAQLQ-AF for use in 8 European countries (Iceland, The Netherlands, Poland, France, Spain, Italy, Greece, and Sweden). METHODS: The English FAQLQ-AF was translated, back-translated, and compared for use in the 8 relevant European languages. Adults with a perceived food allergy were recruited from outpatient departments and through a community survey. Participants completed the FAQLQ-AF, the Food Allergy Independent Measure, and questions concerning participants' characteristics. Validity of the FAQLQ-AF was analyzed for use in the 8 countries. RESULTS: The FAQLQ-AF had strong construct validity (r > 0.59) and an excellent internal consistency (Cronbach α > 0.95) in all countries. Total FAQLQ-AF scores (range 3.2-5.0) were significantly different across participating countries. CONCLUSION: The FAQLQ-AF is a suitable and valid instrument for measuring HRQL in food-allergic adults in Iceland, The Netherlands, Poland, France, Spain, Italy, Greece, and Sweden. The impact of food allergy on HRQL seems to differ among adults from the 8 participating European countries.
Keywords: Adult; Europe; Female; Food Hypersensitivity; Humans; Male; Middle Aged; Quality of Life; Questionnaires